Desempenho competitivo da agricultura no Brasil - Moura, José Ediglê Alcantara (2021)
This dissertation comprises two essays and will deal with competitiveness applied to the Brazilian agricultural context. In the first, the main objective is to analyze the competitive performance of family farming in Brazilian microregions in the period 2006 and 2017. Specifically, it is intended to measure the Family Farming Competitive Performance Index (IDCAF) and group these areas according to the similarities of the IDCAF. Methodologically, factor analysis instruments were adopted using the principal components method and cluster analysis using the non-hierarchical method (k averages), considering data from the 2006 and 2017 Agricultural Censuses, provided by the Brazilian Institute of Geography and Statistics (IBGE). The main results reveal that the determinants of competitiveness of family farming in these micro-regions comprise the following dimensions: traditional competitive management; intensive use of technology in the land factor; agricultural sustainability and modernization. Indeed, there is an expressive heterogeneity in Brazilian family farming, with a concentration of the worst indicators in micro-regions that concentrate a significant rural population, such as the North and Northeast of Brazil. Furthermore, the clusters increased the competitive performance, in average terms, over the time period, and reduced the discrepancy within the considered strata, based on the established parameters. In the second, the general objective is to identify the determinants of competitiveness of family and employer agriculture in the municipalities of Northeastern Brazil. Specifically, it was intended to measure agricultural competitiveness through the Competitive Performance Index of Agriculture in the Northeast (IDCAN); group the municipalities with similar characteristics and relate the determinant factors of competitiveness with the financial resources arising from rural development policies aimed at family farming. o fulfill these objectives, factor analysis techniques were used using the principal components method, cluster analysis using the non-hierarchical method (k averages) and canonical correlations, using data from the 2017 Agricultural Census, National Education Development Fund (FNDE) and Rural Credit Data Matrix (MDCR) of the Central Bank of Brazil (BCB). The main evidence indicates that the majority of northeastern municipalities gave rise to a competitive performance of agriculture at a low and very low level, with patron agriculture performing better than family agriculture. However, the best results for family farming are located in the semi-arid region of the Northeast, notably in the municipalities of state Rio Grande do Norte. On the other hand, the municipalities of Maranhão reached the worst levels of competitiveness, suggesting the relocation of these municipalities with the worst performance in employer and family agriculture to areas similar to the semiarid region with regard to the actions of the Constitutional Fund for Financing of the Northeast (FNE). Due to the above, it was noticed that there is no significant association between the determining factors of the competitive performance of family farming and the financial resources arising from rural development policies, the National School Feeding Program (PNAE) and the National Program for Strengthening Family Farming (Pronaf), indicating the relative lack of effectiveness of these policies, in a systematic way, for gains in the competitiveness of family farming in the Northeast, in accordance with the established parameters.